Effect of a Low-Level Laser on Liposomal Doxorubicin Efficacy in a Melanoma Cell Line: Doxorubicin Delivery Enhancement in Response to Lasers Effect - Razzaghi, Mohammad Reza; Ghazimoradi, Mohammad Hossein; Afzali, Shervin; Kamani, Ehsan; Mohajerani, Ezeddin; Shirkavand, Afshan; Farivar, Shirin (Journal of Lasers in Medical Sciences, 2021)
Introduction: The cytotoxicity of chemotherapy drugs is a significant challenge in the way of surmounting cancer. Liposomal drug delivery has proven to be efficacious in increasing the function of the drugs. Its potential to accumulate drugs in the target site and enhance the efficiency of anticancer agents with lower doses hinders their cytotoxicity on normal healthy cells. Since the release of drugs from liposomes is not generally on a controlled basis, several studies have suggested that external stimuli including lasers could be used to induce controlled release and boost the efficiency of liposomal drug delivery systems (LDDSs). Methods: The A375 cancer cell line was used and exposed to the liposomes containing doxorubicin in the presence of a low-level laser beam to investigate its effect on the liposomal stimuliresponsiveness release and its toxicity on cancer cells. So as to achieve that goal, Annexin V/PI was employed to analyze the number of cells that underwent apoptosis and necrosis. Results: Here, we report the effect of laser irradiation on LDDSs. According to the results obtained from the annexin V/PI assay, the pattern of viability status has shifted, so that the number of preapoptotic cells treated with liposomal doxorubicin and a laser beam was more than that of cells treated with only liposomal doxorubicin. Conclusion: The use of stimuli-responsive LDDSs, in this case, laser-responsive, has led to favorable circumstances in the treatment of cancer, offering enhanced cancer cell cytotoxicity DOI:10.34172/jlms.2021.28